Caracterização morfológica, desempenho produtivo e divergência genética de genótipos de batata-doce - Cavalcante, Marcelo (2008)
Aiming to characterize morphologically the genotypes of sweet potato, to estimate the genetic divergence and to evaluate the yield performance in the edaphoclimatics conditions in the municipality of Junqueiro, Alagoas, Brazil, an experiment was developed, consisting of two varieties and nine clones, in the randomized blocks design with three replications. For morphological characterization, were used 21 descriptors, being fourteen of the shoot and seven of the storage roots. To evaluate the genetic divergence, were used two methodologies: principal components and the generalized Mahalanobis distance, being the genotypes grouped by Tocher method. For the evaluation of the yield performance of the genotypes, were conducted variance analysis, with the averages confronted by Scott-Knott test (P < 0.05). The results indicate there phenotypic variability between the traits of shoot and storage root of the genotypes of sweet potato evaluated. In the estimation of the genetic divergence from principal components analysis, the general form of the mature leaf, the immature leaf color and secondary color of the stem were the traits that most contributed to the divergence of the shoot, explaining 77.08% of the variability existing in the first three principal components. In storage roots, the format, the defect of the surface and the intensity of the predominant color, were the traits that most contributed to the divergence, achieving explain 86.79% of the variability existing in the first three principal components. The acquisition of six groups among the eleven genotypes studied, showed a significant divergence between the genotypes of sweet potato based on the morphological descriptors. When used the generalized Mahalanobis distance methodology, the clone 6 and the variety Sergipana, by their distances of high magnitude, were the most dissimilar (D2 = 244.3). The traits that contributed mostly to the genetic dissimilarity were the marketable root yield (30.79%), the shoot phytomass yield (16.56%) and the internode length (12.84%). The taking of five groups among the eleven genotypes studied showed a significant genetic divergence between the genotypes of sweet potato. The clones 6 and 11 showed the highest marketable roots yield, with 12.08 and 9.08 t ha-1, respectively. The clones 8, 14 and the variety Rainha Prata had the highest shoot phytomass yield, with 5.42, 5.17 and 5.83 t ha-1. These results suggest new prospects for the cultivation of sweet potato in the region of Junqueiro, Alagoas. It was concluded that there is genetic and phenotypic variation among genotypes of sweet potato, explained by morphological characterization and the two techniques to estimate the genetic divergence. According to the results presented in this paper, the Breeding Program of CECA - UFAL may to adopt three measures: the first is the assessment of clones 6 and 11, most yields, in field testing in the municipality of Junqueiro, aiming stability tests, to launch them as varieties. The second will be realization of artificial crosses aiming based in the genetic distances and the per se yields of parents (clones 6 and 8). And the third measure will be the formation of a population with large genetic basis, thereby increasing the probability of obtaining superior genotypes in the segregating generations.